Critical Review—Photostable Fluorescent Cd-Free Quantum Dots Transparently Embedded in Monolithic Silica. (13th September 2019) - Iso, Yoshiki; Isobe, Tetsuhiko
Abstract : Fluorescent Cd-free quantum dots (QDs) such as InP/ZnS and CuInS2 /ZnS have attracted attention for use as color converters for blue light emitting diodes. To protect QDs from oxygen, which degrades them by photo-oxidation during excitation, we fabricated a transparent monolithic silica composite containing the QDs using an aqueous solution of tetramethylammonium silicate (TMAS) as a silica source. The TMAS solution readily dispersed the negatively charged QDs prepared by ligand exchange of 1-dodecanethiol for 3-mercatopropionic acid (MPA). A highly transparent monolithic TMAS-derived silica composite containing the MPA-capped QDs was obtained from the QD dispersion through a sol–gel process. Improved photostability of QDs was explained by the TMAS-derived silica acting as a gas barrier to protect the embedded QDs from photo-oxidation by oxygen in air.